PENGARUH KECERDASAN EMOSIONAL DAN KETERAMPILAN KOMUNIKASI TERHADAP PRESTASI AKADEMIK MAHASISWA PENDIDIKAN BAHASA INGGRIS DI IKIP BUDI UTOMO MALANG - Enis Fitriani (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
This study aimed to determine the effect of emotional quotient (EQ) and communication skill(CS) on student academic achievement (AC). This quantitative studyis explanation type using quota sampling and the analysis used classical assumption test and multiple linear regression analysis.The result of t test showed that both independent variableX1 (EQ) and independent variable X2 (CS) had no effect on dependent variable Y (AC) as evidenced by significance value X1=0.185 (e”0.05) and value significance X2=0.398 (e”0.05). F test results showed that there was no effect between independent variable X1 and independent variable X2 to dependent variable Y simultaneously known from F significance value that is equal to 0.410 (e”0.05). The conclusions are: EQ has no effect on academic achievement; communication skill has no effect on academic achievement; and simultaneously EQ and communication skill have no effect on academic achievement.